Effect of carbonated coarse recycled concrete aggregate on the properties and microstructure of recycled concrete. (1st October 2019) - Lu, Bao; Shi, Caijun; Cao, Zhijie; Guo, Mingzhi; Zheng, Jianlan
Abstract: The effects of carbonated coarse recycled concrete aggregate (RCA) on properties and microstructure of recycled aggregate concrete (RAC) were investigated in this study. The water absorption of 5–10 mm and 10–20 mm coarse RCA was reduced by 30% and 22%, and their corresponding apparent density increased by 4.8% and 3.2% after carbonation treatment. The compressive strength of the concrete with 50% carbonated coarse RCA was 16.7% higher than that with uncarbonated coarse RCA at 28d. A higher replacement ratio of carbonated coarse RCA resulted in higher compressive strength and autogenous shrinkage. However, the drying shrinkage of the RAC with 50% and 100% carbonated coarse RCA was 16.6% and 25.1% lower than that of their respective counterpart prepared with the same amount of uncarbonated coarse RCA. The carbonation treatment effectively improved the micro-hardness of the original interfacial transitional zone (ITZ). All those are due to the reduced the pore sizes and porosity in the matrix and ITZ, and the subsequent reactions between the RCA carbonation products and the cement hydration products, as confirmed by backscattered electron microscope observations.